Risk factors for gastric intestinal metaplasia - Peleteiro,Bárbara (2006)
The infection with Helicobacter pylori affects more than 50% of the world adult population, and approximately two thirds of all cases of stomach cancer are attributed to it, but a large proportion of the infected subjects will never develop cancer. Gastric carcinogenesis is currently interpreted as a multifactorial and multistage process, with environmental exposures (H. pylori infection and behavioural factors), and genetic susceptibility contributing for the occurrence of cancer. The study of the risk factors for precancerous lesions is a major field of research with potential to clarify the aetiology of gastric cancer, namely through the understanding of the mechanisms that modulate the progression to cancer among the infected.